Dihydromyricetin ameliorate postmenopausal osteoporosis in ovariectomized mice: Integrative microbiomic and metabolomic analysis - Xu, Lei; Sun, Xianze; Han, Xiaoqiang; Li, Hui; Li, Xiaoqiong; Zhu, Liying; Wang, Xin; Li, Jinjun; Sun, Haibiao (Frontiers in Pharmacology, 2024)
The gut microbiota may help mitigate bone loss linked to postmenopausal osteoporosis by affecting the immune and inflammatory responses and the gut-bone axis. Dihydromyricetin (DMY), a natural flavonoid, has some anti-inflammatory and antioxidant properties. This study aimed to investigate the mechanisms underlying the amelioration of bone loss in ovariectomized (OVX) mice treated with various doses of DMY. Eight-week-old C57/BL6 mice underwent ovariectomy and received varying DMY doses over 8 weeks. Thereafter, femoral bone microarchitecture, serum biomarker levels, and colon samples were analyzed to assess bone metabolism and inflammatory and hormonal responses. Fecal samples were subjected to 16S rDNA sequencing, and short-chain fatty acids were quantified. An untargeted metabolomics approach was applied to both serum and fecal samples to investigate alterations in the intestinal microbiota and metabolic profiles following DMY treatment in the OVX mice.The results show high-dose DMY has anti-osteoporotic effects. Compared to the OVX group, the DMY-treated group showed enhanced bone mineral density and 2 reduced inflammation and colonic damage levels. The DMY treatment altered the gut microbiota composition, including the relative abundances at both the phylum and genus levels. In addition, DMY treatment increased the production of acetate and propionate. Metabolomic analysis revealed differential regulation of 37 and 70 metabolites in the serum and feces samples, respectively, in the DMY-treated group compared to those in the OVX group, affecting the serotonergic signaling, arachidonic acid metabolism, and unsaturated fatty acid biosynthesis pathways. In conclusion, these findings indicate that DMY can ameliorate bone loss in OVX mice via the gutbone axis.